KNOWLEDGE WITH LECTURER BEHAVIOR ABOUT COMPETENCE BASED CURRICULUM LEARNING METHODE (Studi On Stikes Icme Jombang) - Deni Indra Prasetyo; Arif Wijaya; Yunan Yusuf Habibi (JIWA INTER PLUS, 2011)
Learning Competency Based Curriculum requires that the learning process should be student centered learning. The learning process should provide an opportunity and a larger space for students to explore, to experience, discover, and also test their own comprehension by asking and constantly questioning what is learned. Learning Competency Based Curriculum models that is : Small Group Discussion, Role-Play & Simulation, Discovery Learning (DL), Cooperative Learning (CL), Problem Based Learning. The purpose of this study was to analyze the relationship between knowledge about the behavior of faculty teaching methodKBK at STIKES ICME Jombang. The design of this study used an observational study conducted by cross sectional analytical cross sectional. This study was conducted in STIKES ICME Jombang, total sampling method with a sample of 74 lecturers during the study but only 35 respondents. Data collection using questionnaires. Analysis of the data using statistical test product moment correlation, with probability value as 0,011 more than value α (0,05), in order to H1 accepted The results showed that there is a correlation with the behavior of faculty knowledge about teaching methods KBK in STIKES ICME Jombang. Knowledge has a relationship with professors about the behavior of the learning method KBK in STIKES ICME Jombang. Sugestion STIKES ICME Jombang expected to contribute ideas in terms of teaching and learning activities, so that the learning process more effective and efficient.